Analisis Perbandingan Kinerja Keuangan Perusahaan BUMN Industri Farmasi Sebelum Dan Sesudah Holding Periode 2018-2022 - Sabar Hasiholan Manalu; Murtanto Murtanto; H Lutfi Baradja (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research was conducted to examine and obtain a comparison of the performance of state-owned pharmaceutical industry companies before and after the formation of the holding company. Based on the results of research conducted, the author uses the results of the total asset turnover ratio (TATO), Net Profit Margin (NPM), Return on Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio ( CR). The method used in this research is a descriptive and comparative method using a quantitative approach. The results of this study show that there are differences in the financial performance of pharmaceutical industry holding companies as measured by the Total Asset Turnover ratio before and after Holding, there are differences in the financial performance of pharmaceutical industry holding companies as measured by the Net Profit Margin ratio before and after Holding, there are differences in financial performance pharmaceutical industry holding companies as measured by the Return On Asset ratio before and after Holding, there is no difference in the financial performance of pharmaceutical industry holding companies as measured by the Return On Equity ratio before and after Holding, there is no difference in the financial performance of pharmaceutical industry holding companies as measured by the ratio Debt to Equity Ratio before and after Holding, and there are differences in the financial performance of pharmaceutical industry holding companies as measured by the Current Ratio before and after Holding.